CPA Examination: Accounting Practice. - Chamberlain, John H. (The Accounting Review, 1967)
Abstract This article presents a list of problems that were prepared by the Board of Examiners of the American Institute of Certified Public Accountants (CPA) and were presented as the second half of the CPA examination in accounting practice on November 3, 1966. The candidates were required to solve the first four problems and either problem five or six. Time allocated for first problem is 30 to 40 minutes, second problem is 50 to 60 minutes, third problem is 40 to 50 minutes, fourth problem is 50 to 60 minutes and 5th or 6th problem is 50 to 60 minutes. All questions are pertaining to the taxation of partnerships and the answer is to be selected in accordance with the current internal revenue code and regulations. Examinees are instructed to select one answer for each question and their grade will be determined from their total score of correct answers. In the end of the test solutions are also provided to help the examinee. All the questions of the test deals with the internal revenue code and regulations.